Effect of Cognitive Strategies Training on Nursing Students' Academic Achievement in School of Nursing and Midwifery of Iran University of Medical Sciences Based on Kirk-Patrick Model - Mohammad Hasan Keshavarzi; Daryadokht Masroor-Roodsari; Leila Janani; Atefe Zabihi zazoly (Zanjan University of Medical Sciences and Health Services, 2019)
Background & Objective: Nowadays, the academic achievement of students is one of the concerns of professors and authorities. Therefore, the training courses are expected to be designed so that students can achieve this goal as one of the indicators of educational system effectiveness. Hence, in this study, we try to use cognitive strategies training for nursing students' academic achievement and the impact of this training is examined by applying the Kirk-Patrick model. Materials and Methods: This quasi-experimental study was performed on 60 nursing students (two groups of 30 students) of Iran University of Medical Sciences. In the experimental group, in addition to presenting the content of the lesson, 5 sessions of 20 minutes were presented and practiced in the form of the extracurricular cognitive strategies program. The data collection tool was pre-test and post-test (end-of-course test). Data were analyzed by SPSS software version 20. Results: All 60 students participated in the study. There was no significant difference between the scores of students in the two groups before the cognitive strategies training (P = 0.1). There was a significant difference between the scores of the two groups after intervention and training (P = 0.001). Moreover, paired t-test results showed that the mean scores of post-test in each group increased compared to the pre-test but this increase was higher in the experimental group than the control group (P = 0.001). Conclusion: Training the cognitive strategies will lead to students' academic achievement so that planning is recommended for training and promotion of these strategies.